PENGARUH KUALITAS PRODUK, CITRA MEREK, DAN DESAIN PRODUK TERHADAP KEPUTUSAN PEMBELIAN IPHONE DI KOTA BATAM - Syam, Putra (LPPM Universitas Putera Batam, 2025)
The smartphone industry in Indonesia continues to experience significant growth along with technological developments and changes in people's lifestyles. In recent years, smartphones have become a basic need for most people, not only as a communication tool, but also as a means of supporting daily activities such as working, studying, shopping, and entertainment. This study aims to analyze the influence of product quality, brand image, and product design on iPhone purchasing decisions in Batam City. This study uses a quantitative method. With the technique of determining the number of samples using the Jacob Cohen formula with 204 respondents. The data used in this study were collected through questionnaires distributed in Batam City. The data analysis technique used in this study is multiple linear regression, which is then tested through data quality tests, classical assumption tests, influence tests and hypothesis tests. The findings of this study in the T test indicate that product quality has a positive and partially significant effect on iPhone purchasing decisions in Batam City, brand image has a positive and partially significant effect on iPhone purchasing decisions in Batam City, and product design has a positive and partially significant effect on iPhone purchasing decisions in Batam City. The F-test findings indicate that product quality, brand image, and product design simultaneously have a positive and significant influence on iPhone purchasing decisions in Batam City.